Study of Biodiversity of Arbuscular Mycorrhizal Fungi in Addition with Different Organic Matter in Different Seasons of Kavre District (Central Nepal) - Vaidya, Geeta Shrestha; Shrestha, Keshab; Khadge, Buddhi R; Johnson, Nancy C; Wallander, Håkan (Scientific World, 2010)
Different types of organic matter (dried and powdered 5 gms. leaves of Tithonia diversifolia, Eupatorium adenophorum, Lantana camara, farmers compost) and triple-superphosphate were mixed with eroded soil collected from sites with no vegetation. Eroded soil without amendments served as control. The mixture was placed in mesh bags (50 Mm mesh) that allowed fungal colonization but excluded roots. Two sets of mesh bags were buried around Bauhinia purpurea and Leucaena diversifolia that had been planted in an eroded site. The first set was buried in June 2003 and harvest in December 2003 (the monsoon period) and the second set was buried in December 2003 and harvested in June 2004 (The drier period). We found that more Arbuscular mycorrhizal (AM) fungal biomas and spores were produced during the wet season than during the dry season. The different types of organic matter had similar influence on the amount of AM biomass but the species composition was varied with the types of organic matter. In wet season nine species of AM spores and in dry season ten species of AM spores were found. In dry season Scutellospora nigra was found which was different from wet season. Key words: Arbuscular mycorrhiza; Organic matter; Wet season; Dry season. DOI: 10.3126/sw.v5i5.2660 Scientific World, Vol. 5, No. 5, July 2007 75-80